The dsRNA of Trichomonas vaginalis is associated with virus-like particles and does not correlate with metronidazole resistance - Flegr, J; Cerkasov, J; Kulda, J; Tachezy, J; Stokrová, J (Folia microbiologica, 1987)
Twelve metronidazole-resistant and twelve metronidazole-susceptible strains of Trichomonas vaginalis were tested for the presence of dsRNA. Three resistant and five susceptible strains were found to contain dsRNA which indicated that metronidazole resistance does not correlate with the absence of dsRNA. Electron microscopy showed the homogenates of all dsRNA-positive strains to contain virus-like particles 32-38 nm in diameter, while no such particles were found in the dsRNA-negative strains. A mutual relationship between the dsRNA and virus-like particles seems to exist.
Keywords: Trichomonas vaginalis; Metronidazole; dvouvláknová RNA; Drug Resistance; DNA virů; RNA, Double-Stranded; DNA, Viral; Animals; metronidazol; léková rezistence; zvířata